The Impact of Banking Competition on Enterprise Digital Intelligence Transformation - Mou, Ruoqi (Transactions on Economics, Business and Management Research, 2024)
Against the backdrop of a new wave of digital intelligence transformation, advancing the digitalization of enterprises in China to accelerate industrial upgrading and empower high-quality economic development has garnered significant attention. This study focuses on listed companies from 2002 to 2022 and finds that competition in the banking sector significantly promotes the digital intelligence transformation of enterprises by alleviating financing constraints. The easing of financing constraints induced by banking competition enhances the subjective willingness of enterprises to engage in research and development activities. Moreover, increased competition among banks facilitates maintaining favorable relationships between banks and enterprises, thereby helping enterprises gain more information and financial support during the process of digital intelligence transformation. Thus, it promotes the digital intelligence transformation of enterprises effectively.